Does students' thought structure in object configuration patterns follow cognitive verbs in learning outcomes? - Dahlan, Jarnawi Afgani; Nurlaelah, Elah; Bariyah, Nusrotul; Kristiani, Yasinta Dian (IKIP Siliwangi and I-MES, 2025)
This study aims to comprehensively investigate students' learning approach in identifying, predicting, and generalizing object and number configuration. A qualitative method was applied with as many as 28 participants from eighth-grade students in Bandung, Indonesia. Students’ ability to recognize, predict, and generalize the configuration of objects and numbers was assessed. At the same time, the approaches employed in the process were analyzed. The research showed that students used different approaches to figure out the pattern of objects and number configuration. These approaches were: descriptive, operational, visual-descriptive, visual-operational, and descriptive-visual-operational. Keywords were typically employed in the descriptive approach to predict unknown objects or numbers. However, the descriptive approach could not accurately predict specific patterns. Therefore, students employed other approaches, including operational, visual-descriptive, visual-operational, and descriptive-visual-operational approaches. Unfortunately, all approaches have proven inadequate for formulating generalizations (general rules) independently. These results showed that when teaching students how numbers and objects are configured, they should be encouraged to try different ways of seeing patterns, such as descriptive, visual, operational, or a combination of the three.